Histoire contemporaine et engagements politiques - Maurice Agulhon (Mélanges de la Casa de Velázquez, 2004)
The author regrets the partial and recent nature of his knowledge of Spain. He challenges the title «The historian of the Republic» as being too simplistic. His work does not convey a coherent project; on the contrary, it has undergone more of a fortuitous reorientation, either by chance or due to the instructions of the editor. Themes which are quite different to that of «The Republic» appear in it, only to be abandoned sometimes («Sociability») or else widened into other areas («Symbolism»). He goes on to explain his encounter with the main themes in the interpretation of history (Karl Marx, Michel Foucault, François Furet) whose philosophical contribution needs to be acknowledged and to discuss its influence in historiography. The complexity of what is factual does not fit in well with abstract constructs, even when derived from the most inspired intuition.